Islamic Work Ethics and Gender Equality: Navigating Professionalism and Inclusivity in the Indonesian Muslim Workforce - Sekhani Dewi Ana; Axsel Nicolas Friansah; Sumarta; Rosidin (Lentera Peradaban: Journal on Islamic Studies, 2025)
This research explores the relationship between Islamic work ethics and gender equality within the professional sphere of Muslim society, with a specific focus on the Indonesian context. The study is motivated by the persistent challenges faced by Muslim professional women, including patriarchal norms, gender stereotypes, domestic expectations, and organizational policies that lack gender sensitivity. Islam emphasizes the principles of justice ('adl), trustworthiness (amanah), equality (musawah), and responsibility, which possess the potential to serve as the moral and professional foundation for an inclusive and gender-equal workplace. Using a qualitative approach, this study employs literature review and contemporary discourse analysis. Primary data are derived from Islamic foundational texts (the Qur’an, Hadith, and maqāṣid al-sharīʿah), while secondary data consist of empirical and contemporary literature on Muslim women, Islamic work ethics, and their implementation in formal and informal organizations. A thematic analysis was conducted to examine Islamic work values, cultural and structural barriers, and gender equality practices in the workforce. The results indicate that the values of amanah, honesty, responsibility, justice, and musawah significantly support organizational productivity, integrity, and inclusivity. However, practical implementation remains hindered by entrenched patriarchal culture, gender stereotypes, and rigid organizational structures. The study concludes that the application of gender-responsive Islamic work ethics requires a holistic strategy that integrates organizational policy, ethical and gender education, and a transformation of work culture. This research provides both theoretical and practical contributions by enriching academic literature and offering guidance for organizations to achieve gender equality based on Islamic principles